THE INFLUENCE OF USING BELIVE IT OR NOT GAME TO IMPROVE STUDENTS' READING ABILITY - Arif Wicaksono, Garda (Aisyah Journal of English Language Teaching (AIJELT), 2022)
The objective of the research was to find out the influence of Believe it or not games. In this research, the researcher used a quantitative method research design by using an experimental design. For the main technique, the researcher uses a multiple choices test which test consists of 50 items tests each item consisted of five options A, B, C, and D. In this research shows that in data analysis the researcher uses a T-test and got that t test≥ t-table: 6.82≥2.00 and 6.82≥2.66. So, Ho is rejected and Ha is accepted. So, it concluded that teaching reading through Believe it or not the game has a significant influence on students’ reading ability.